2018
DOI: 10.18203/2349-3291.ijcp20181522
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile and outcome of pediatric poisoning: a prospective observational study from a tertiary care center

Abstract: Background: Acute poisoning in children is one of the common causes for emergency hospital visit in developing countries. Objectives of the present research was aimed to study the magnitude, nature, age, sex, socioeconomic status and outcome of poisoning in children aged <15 years.Methods: This prospective study was conducted for a period of 1 year between January 2017 to December 2017, at S.V.S. Medical College and Hospital, Mahabubnagar, Telangana. All poisoning cases under the age of 15 years were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Eighty percent of the cases were of accidental nature in our study which matches with the studies done by Reddy et al and Sahin et al [11,12] Twenty percent cases were not of accidental nature. They were either intentional or homicidal in nature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eighty percent of the cases were of accidental nature in our study which matches with the studies done by Reddy et al and Sahin et al [11,12] Twenty percent cases were not of accidental nature. They were either intentional or homicidal in nature.…”
Section: Discussionsupporting
confidence: 91%
“…[2] Similar results were obtained in a study conducted by Reddy et al, where 53.1% were male. [11] However, the study conducted by Sahin et al reported that the majority were female (51.6%). [12] It is difficult to interpret which gender is vulnerable in the Indian context with changing socioeconomic scenario, the gender gap in poisoning may not be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, studies by Aggarwal et al and Manikyamba et al showed the incidence of acute poisoning among the paediatric population in tertiary care centres as 2.1% and 2.8%, respectively [9,15]. Also, the proportion of children who needed PICU admission was similar to the studies by Reddy et al and Selvakumar et al [16,17].…”
Section: Discussionsupporting
confidence: 91%
“…The contribution of acute poisoning cases to total admissions PICU is comparable to earlier studies conducted in various part of India. 6,13,14 The lower figures also have been reported. 5,15,16 They may be due to taking total pediatric admissions as denominator.…”
Section: Discussionmentioning
confidence: 71%